Analysis of Assessment Instruments Used in Foreign Language Teaching (2004)
ABSTRACT: This article presents partial results of a research project on foreign language teachers’ discourse and practices with respect to assessment, the aim of which is to improve teachers’ assessment practices. The study, conducted in two Colombian universities, has various components: analysis of documents interviews with teachers and students, and workshops with participating teachers in order to qualify them and agree on an improved assessment system. In this report we discuss the analysis made of tests, grids, registers, and forms and other kinds of instruments that teachers use to assess their students. For the analysis of instruments we used an inductive-deductive procedure whereby categories emerging from a first analysis of instruments were then refined by comparing them to those proposed by Bachman and Palmer (1996) and other authors. In general, teachers seem to prefer “hard” over “soft” types of assessment. Moreover, the qualities of assessment on which they seem to rely the most are practicality and reliability; and the ones least taken into consideration are authenticity and interactivity.